The Effect of Implementing the E-Billing System on Taxpayer Compliance at the KPP Pratama Yogyakarta with Understanding of Internet Technology as a Moderating Variable - Herowati, Erlina; A Hilda Syahrani (Indonesian Journal of Interdisciplinary Research in Science and Technology, 2025)
This research aims to analyze the effect of implementing the E-Billing system on the level of individual taxpayer compliance at KPP Pratama Yogyakarta, with an understanding of internet technology as a moderating variable. The implementation of the E-Billing system is expected to increase the efficiency and effectiveness of tax payments, as well as reduce the error rate in tax reporting. However, the level of success of this system is very dependent on the taxpayer's level of understanding of internet technology. The research method uses quantitative methods with a survey approach. The sample in this study consisted of individual taxpayers registered at KPP Pratama Yogyakarta. Data was collected via questionnaire to 70 respondents selected using the purposive sampling method. Data analysis was carried out using multiple linear regression and the Moderated Regression Analysis (MRA) test to determine understanding of internet technology as a moderating variable. The research results show that the implementation of the E-Billing system has a positive and significant effect on the level of taxpayer compliance. In addition, understanding internet technology has been proven to strengthen the relationship between the implementation of the E-Billing system and taxpayer compliance. This research contributes to the Directorate General of Taxes (DJP) in improving strategies for implementing digital-based taxation systems and as a reference for taxpayers in increasing their understanding of technology to maximize the use of the E-Billing system.